Directly Imaging Dynamic Electronic Coupling during Electrochemical Oxidation of Single Silver Nanoparticles. (25th August 2022) - Jiang, Bo; Gu, Wenjie; Jiang, Wenxuan; Lv, Mengqi; Niu, Ben; Wu, Xue‐Jun; Wang, Wei; Wang, Hui
Abstract: The electronic coupling between a metal electrode and single nano‐entities is of unfading significance which impacts the heterogeneous electron transfer. Herein, we demonstrated a simple optical technique for directly imaging the transient interfacial electronic coupling events during electrochemical oxidation of single Ag nanoparticles on Au electrode. The electronic coupling brings out a dramatic dip behavior of bright field imaging traces, and is conductive to cross the energy barrier of oxidation for single silver nanoparticles. This dip behavior is further verified by in situ vis‐transmission spectroscopy, and the heterogeneity of the Au−Ag electronic coupling down to single‐nanoparticle level is uncovered by unifying the morphology and size of individual silver nanoparticles. These results suggest the interfacial electronic coupling facilitates electron transfer of single nanoparticles, and provide important insight into understanding detailed mechanism of nanoelectrochemistry. Abstract : During electrochemical oxidation processes, a dip behavior for single Ag nanoparticles on Au electrodes is directly visualized using a monochromatic bright field imaging technique. This observation can be attributed to interfacial Au−Ag electronic coupling interactions, which are manifested as the heterogeneity of electrochemical activity of individual Ag nanoparticles.